1992
DOI: 10.1111/j.1471-4159.1992.tb09429.x
|View full text |Cite
|
Sign up to set email alerts
|

MK‐801 Prevents 1‐Methyl‐4‐Phenyl‐1,2,3,6‐Tetrahydropyridine‐Induced Parkinsonism in Primates

Abstract: In cynomologus monkeys, systemic administration of MK-801, a noncompetitive antagonist for the N-methyl-D-aspartate receptor, prevented the development of the parkinsonian syndrome induced by the neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). MK-801 also attenuated dopamine depletion in the caudate and putamen and protected dopaminergic neurons in the substantia nigra from the degeneration induced by the neurotoxin. Nevertheless, 7 days after MPTP administration in the caudate and putamen of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(55 citation statements)
references
References 28 publications
5
49
0
1
Order By: Relevance
“…These results are in accordance with findings obtained using the non-competitive NMDA antagonist MK-801 in another primate species (Zuddas et al 1992). A neuroprotective effect has been observed at the morphological level, i.e.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in accordance with findings obtained using the non-competitive NMDA antagonist MK-801 in another primate species (Zuddas et al 1992). A neuroprotective effect has been observed at the morphological level, i.e.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with this model, rodent studies have demonstrated that lesions of the STN decrease the 6-hydroxydopamine-induced degeneration of SNc neurons (Piallat et al, 1996). Furthermore, N-methyl-D-aspartate antagonists have been found to decrease the 1-methyl-4-phenylpyridiniuminduced degeneration of SNc neurons (Turski et al, 1991) as well as 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-induced degeneration of SNc neurons in primates (Zuddas et al, 1992). Interestingly, direct application of (Ϫ)-5-methyl-10,11-dihydro-5H-dibenzo[a,d]cyclohepten-5,10-imine maleate (MK801) in the rat STN has been found to block the 6-hyrdoxydopamine-induced degeneration of SNc neurons (Blandini et al, 2001).…”
Section: Discussionmentioning
confidence: 70%
“…31,192 The STN is the main excitatory structure of the basal ganglia 151 and has efferences in the SNc. 150 It was originally hypothesized that STN overactivity in PD could contribute to progression of the disease 4,150 and its inactivation may slow or prevent it.…”
Section: Neuroprotectionmentioning
confidence: 99%